Relationship Between Obesity And Parasympathetic Nerve Function - Akhtar, Shahin; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2009)
Back ground: Obesity is a potential risk factor for cardiovascular morbidity and mortality. As certain cardiovascular disorders associated with autonomic nerve which dysfunction often coexist in obese persons, investigations of autonomic nerve function especially parasympathetic nerve function in obese, for detection of early autonomic impairment can be potentially important to prevent complications. Objective: The present study was done to observe the parasympathetic nerve function status in obese persons in order to investigate the relationship of autonomic nerve function with obesity. Study design: This study was conducted in the department of Physiology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh during July 2006-June 2007. For these 40 apparently healthy obese subjects of both sexes with BMI â¥ 25 kg/sqm. were included in study group. Age and sex matched 40 apparently healthy non obese subjects with BMI range 18.5-22.9 kg/sqm. were taken as control for comparison. Methods: To assess parasympathetic nerve function status, heart rate response to valsalva(valsalva ratio), heart rate response to deep breathing and heart rate response to standing (30th:15th ratio) were determined by 3 noninvasive cardiovascular reflex tests. Data were collected by recording ECG of all subjects under test condition. The correlations of these parasympathetic nerve function parameters with BMI were also studied. Unpaired Student ât' test and Pearson correlation coefficient test were used for statistical analysis. Results: Valsalva ratio (1.47Â±0.24 vs 1.67Â±0.31), HR response to deep breathing (19.62Â±5.55 vs 27.59Â±6.51) and HR response to standing (1.07Â±0.07 vs 1.13Â±0.018) were significantly decreased in obese subjects than those of non obese control. All these parameters were negatively correlated with BMI. and these relatioship were statistically significant. Conclusion: The results of this study indicate that parasympathetic nerve function may be reduced in apparently healthy obese subjects. Key words: Obesity; valsalva; parasympathetic; deep breathing. Â doi: 10.3329/jbsp.v3i0.1797 J Bangladesh Soc Physiol.2008 Dec;(3):50-54.